Hippocampus mediates nocebo impairment of opioid analgesia through changes in functional connectivity. (16th June 2022) - Bingel, Ulrike; Wiech, Katja; Ritter, Christoph; Wanigasekera, Vishvarani; Ní Mhuircheartaigh, Roisin; Lee, Michael C.; Ploner, Markus; Tracey, Irene
Abstract: The neural mechanisms underlying placebo analgesia have attracted considerable attention over the recent years. In contrast, little is known about the neural underpinnings of a nocebo‐induced increase in pain. We previously showed that nocebo‐induced hyperalgesia is accompanied by increased activity in the hippocampus that scaled with the perceived level of anxiety. As a key node of the neural circuitry of perceived threat and fear, the hippocampus has recently been proposed to coordinate defensive behaviour in a context‐dependent manner. Such a role requires close interactions with other regions involved in the detection of and responses to threat. Here, we investigated the functional connectivity of the hippocampus during nocebo‐induced hyperalgesia. Our results show an increase in functional connectivity between hippocampus and brain regions implicated in the processing of sensory‐discriminative aspects of pain (posterior insula and primary somatosensory/motor cortex) as well as the periaqueductal grey. This nocebo‐induced increase in connectivity scaled with an individual's increase in anxiety. Moreover, hippocampus connectivity with the amygdala was negatively correlated with the pain intensity reported during nocebo hyperalgesia relative to the placebo condition. Our findings suggest that the hippocampus links nocebo‐induced anxiety to a heightened responsiveness to nociceptive input through changes in its crosstalk with pain‐modulatory brain areas. Abstract : Using fMRI, we previously showed that hippocampal activity correlates positively with a nocebo‐induced impairment of opioid analgesia in healthy human volunteers. Here, we follow up on these findings by showing that these nocebo‐related changes are linked to an increase in hippocampal functional connectivity with posterior insula, periaqueductal grey and primary somatosensory/motor cortex (SI/MI) that scaled with ratings of anxiety and to a decrease in connectivity with the amygdala that scaled with pain intensity ratings.